Combined FIR and Fractional-Order Repetitive Control for Harmonic Current Suppression of Magnetically Suspended Rotor System - Cui, Peiling; Wang, Qirui; Li, Sheng; Gao, Qian (IEEE transactions on industrial electronics (1982), 2017)
Magnetically suspended rotor has the characteristics of no friction and active vibration control. The mass unbalance and sensor runout of the rotor induce harmonic current, which will cause harmonic vibration. The ratio of the sampling rate to the fundamental frequency of harmonic current is often not an integer. The existing repetitive control (RC) for the suppression of harmonic current in magnetic bearing is applicable for the integer case. Harmonic current suppression performance is degraded drastically if the ratio is fractional. In this paper, combined finite-impulse response (FIR) and fractional-order RC is proposed. FIR filter and fractional-order RC are combined to perform harmonic current suppression at arbitrary frequency. Phase compensator is designed to enhance the stability of magnetically suspended rotor system. Experimental results are given to verify the effectiveness and superiority of the proposed method.